Quercetin inhibits fibroblasts proliferation and reduces surgery-induced epidural fibrosis via the autophagy-mediated PI3K/Akt/mTOR pathway. Issue 4 (1st April 2022) - Cao, Yile; Chen, Hui; Sun, Yu; Fan, Zhehao; Cheng, Hong
ABSTRACT: Epidural fibrosis (EF) is a serious complication when the patients suffer from operations of lumbar laminectomy. It is reported that quercetin plays a positive role in the prevention of various fibrotic diseases. However, the role of quercetin in the prevention of epidural fibrosis (EF) and its possible mechanism are unclear. Fibroblast proliferation is considered to be the main cause of epidural fibrosis.Autophagy is a lysosomal degradation pathway that is essential for survival, differentiation, development, and homeostasis.Although autophagy has been associated with fibrosis of different tissues, the effect of autophagy on epidural fibrosis is still unknown.The aim of this study was to investigate the function and mechanism of autophagy induced by quercetin, a polyphenol derived from plants. In vivo, the effect of quercetin on reducing epidural fibrosis was confirmed via histological staining and immunohistochemical analysis. The results showed that quercetin had significant suppressive effects on epidural fibrosis following laminectomy in rats.In vitro, , cell counting kit-8 (CCK-8), Western blot analysis, immunofluorescence and Edu staining, TUNEL staining and transmission electron microscopy were used to detect the effects of quercetin on the proliferation and apoptosis of fibroblasts and explore the possible signal transduction pathway. Results indicated that quercetin could induce autophagy and inhibit proliferation in fibroblasts. In conclusion, Quercetin could regulate fibroblast proliferation, apoptosis, migration and other biological behaviors through autophagy, thereby preventing epidural fibrosis. The specific corresponding pathway may be the PI3K/Akt/mTOR signaling pathway. Graphical abstract: uf0001